PENGARUH MODEL PEMBELAJARAN TREFFINGER TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Saripudin, Muhammad; Soeprianto, Harry; Hikmah, Nurul; Arjudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out whether there is an influence of the treffinger learning model on students' mathematical creative thinking skills on the building materials of flat-sided spaces for grade VIII students of SMPN 4 Narmada for the 2023/2024 school year. This research is included in quantitative research with a type of quasi experimental design research. The population in this study was all grade VIII students at SMPN 4 Narmada for the 2023/2024 school year with samples of classes VIII A and VIII B taken using a simple random sampling technique. The instruments in this study are observation sheets and tests of students' mathematical creative thinking abilities as well as data analysis techniques using valid tests, namely normality tests, homogeneity tests and hypothesis tests. The results of this study show that there is a difference in the average score of mathematical creative thinking ability of students who use the treffinger learning model and students who use the conventional learning model. So this shows that there is an influence of the treffinger learning model on students' mathe matical creative thinking skills in the building materials of flat-sided spaces for grade VIII students of SMPN 4 Narmada for the 2023/2024 school year.